Rethinking the role of land privatization in peri-urban transformations in Ukraine: the case study of Sokilnyky, Lviv oblast - Lozynskyi, Roman (Human Geography Journal, 2019)
The purpose of the study is to find out how the distribution and further privatization of land have affected the changes of peri-urban villages in Ukraine since the 1990s, based on the case of the village of Sokilnyky near Lviv. After the collapse of the Soviet Union and the redirection of Ukraine’s economy from a planned centralized to a market-oriented crony-capitalism, the peri-urban areas of largest cities have become complex, dynamic and contradictory spaces with drastic changes in demography, housing, infrastructure, and land use. The shift of land policy in Ukraine in the 1990s with the weakening of planning regulations and the way land was distributed are the main triggers of how peri-urban areas have been transforming. The analysis of changes in land ownership, household farming/agriculture, detached houses’ number and size, household income and urban morphology (street network, location of houses and commercial units) in Sokilnyky since 1990s reveals three key consequences of privatization and commodification of land in post-socialist cities’ environs: a) land privatization provided the opportunity for small-scale household farming/agriculture for one class of people as a survival strategy, especially during the economic crisis of the 1990s, and a place for housing and commercial construction for another, causing the eclectic nature of peri-urban settlements with mixing different classes of people with different lifestyles; b) land distribution and privatization were crucial in the emergence of chaotic, fragmented and ad-hoc housing and commercial units, since land division into plots in the 1990s preceded urban planning and master plan development; c) privatization has also created a condition for biased land-development for profit, resulting in shrinkage of public spaces, communal lands and green open spaces. The study is based on statistics from local government, historical map analysis, informal interviews/personal communication with urban planners and officials, and fieldwork visual analysis.